The aesthetics of atheism : theology and imagination in contemporary culture - Callaway, Kutter, 1979-; Taylor, Barry, 1951- (Fortress Press, 2019)
Atheism and Christianity are often placed at polar opposite ends of a spectrum, forever in stark conflict with each other. In The Aesthetics of Atheism, Kutter Callaway and Barry Taylor propose a radical alternative: atheism and theism need each other. In fact, atheism offers profound and necessary theological insights into the heart of Christianity itself. To get at these truths, Callaway and Taylor dive into the aesthetic dimensions of atheism.